Engineered magnetic nanoparticles as efficient sorbents for wastewater treatment: a review. (10th November 2018) - Gupta, Nikesh; Pant, Parul; Gupta, Chetna; Goel, Puneet; Jain, Astha; Anand, Sakshi; Pundir, Anuj
Abstract: With the rapid advancement of economics, world's water resources have been adversely affected by various contaminants like microbes, organic dyes and heavy metal ions. Eventually, this is the sole reason for number of environmental problems. Researchers have always been paying much attention towards water treatment and utilisation of magnetic nanoparticles (MNPs) as nanosorbents for the same. Moreover, MNPs based immobilisation technology for enhanced and efficient removal proves to be an innovative research point. This is due to unique properties of nanoparticles like extremely small size, high surface area to volume ratio, surface modifiability and great biocompatibility. This review outlines the interesting pathways of removing water impurities. It also gives a compendious overview of the research progress achieved in the very field of wastewater treatment using MNPs, along with some important methods of their synthesis. Abstract : Graphical abstract